1999
DOI: 10.1177/108056999906200404
|View full text |Cite
|
Sign up to set email alerts
|

Content of the Business Communication Course: An Analysis of Coverage

Abstract: This study examined 229 responses from members of the Association for Business Communication (United States) who rated the importance of 30 business commu nication concepts. The concepts were divided into six categories: communication theory, written communication, oral communication, employment communica tion, technology, and current business communication issues. Respondents also reported the amount of class coverage they provided for each topic. Of the 30 con cepts, 23 were rated as moderately or greatly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 4 publications
3
53
2
Order By: Relevance
“…However, stand-alone courses with a written focus significantly outnumber those with an oral focus. This aligns with the survey finding by Wardrope and Bayless (1999) that written communication received more attention in business communication courses than oral communication.…”
Section: Course Contentsupporting
confidence: 90%
See 2 more Smart Citations
“…However, stand-alone courses with a written focus significantly outnumber those with an oral focus. This aligns with the survey finding by Wardrope and Bayless (1999) that written communication received more attention in business communication courses than oral communication.…”
Section: Course Contentsupporting
confidence: 90%
“…The survey had approximately a 20% response rate with 229 responses and collected data regarding instructor coverage of the following areas: communication theory, written communication, oral communication, technology issues, employment communication, and current issues. Wardrope and Bayless (1999) found that the majority of business communication courses were taught within business colleges rather than by other Although these studies based on survey methodology are not directly comparable to Knight's study of exemplary programs or to the study we report here, some similar findings are suggestive of patterns in business communication curricula. First, all of the studies indicate that business communication courses tend to be taught within the business college; this finding also aligns with a 1998 study conducted by Kleen and Gros (as cited in Ryan, 1999), who surveyed deans at 335 AACSB accredited schools.…”
Section: A Review Of Previous Studiescontrasting
confidence: 80%
See 1 more Smart Citation
“…Figure 2 charts the percent of respondents for the composite written skill items. Specifically, for each group of respondents the total good rating responses for the four survey items under the written skills category was divided by the number of respondents; the same calculation was made by group for the acceptable and poor ratings of written communication skills.. (Wardrope & Bayless, 1999). Although both employers and faculty rated written grammar and punctuation skills the lowest of the twelve items (Table 1), only 11 % of employers indicated the skill level of poor; 44 % of employers indicated written grammar and punctuation skills as good for a combined total of 89 % rated employees as acceptable to good.…”
Section: Discussionmentioning
confidence: 99%
“…-' Due to widespread public speaking anxiety and the importance of oral communication ability (Wardrope & Bayless, 1999), two approaches were used to address these problems. First, an inexpensive supplementary text (Motley, 1997) specifically directed to public speaking anxiety was required.…”
Section: Pedagogical Activitiesmentioning
confidence: 99%